Influence of repeating sequence on structural and thermal stability of crystalline domain of bombyx mori silk fibroin - Aksakal, Baki; Akdere, Unsal; Gunay, Seckin D.; Cagin, Tahir; Tasseven, Cetin (IOP Publishing Ltd, 2019)
Thermophysical properties of polar-antiparallel beta-sheet crystalline domains of B.mori silk fibroin has been investigated via molecular dynamics (MD) simulations between 300 K and 700 K. In general, the type of interactions determines the character of the thermal expansion in corresponding directions except that the crystalline domains with serine residue contracts along the chain direction resulting with a negative thermal expansion (NTE) coefficient of alpha(y) approximate to -10(-4) K-1 at 300 K. The heat capacity at constant pressure C-P increases sublinearly up to about 650 K with an almost continuous decrease in the rate of change of entropy (dS/dT)(P). Energetic behavior of the beta-sheet crystalline units is determined by the main chain below 400 K then thermally activated motion of side chain (HG1) of serine residue becomes effective up to the degradation point. These are particularly important in designing thermally controlled composite materials.
Keywords: B.mori silk fibroin; beta-sheet crystallite; MD simulation; thermophysical properties; BETA-SHEET CRYSTALS; MECHANICAL-PROPERTIES; TENSILE PROPERTIES; FIBER FORMATION; SPIDER; NANOSTRUCTURE; DEPOSITION; EFFICIENT; COMPONENT; HEAVY; Materials Science